Experimental studies in reinforced concrete transfer beams for high-rise buildings - Mohan Rao, B. D. V. Chandra; Rao, N. V. Ramana (Journal of Structural Engineering, 2025)
Results of the detailed experimental investigation on the behavior and ultimate shear strength of reinforced concrete Transfer (deep) beams in high-rise buildings are summarized. The concrete compressive cube strength is 6235 psi (43 MPa). The test results are divided into three series based on the shear span-to-effective depth ratio, a/d, ranges from 1.10 to 3.20, longitudinal and vertical steel/s ratio. Series-I specimens consists of five beams with different depths in terms of shear span-to-depth ratio, and Series-II specimens consists of five beams with constant shear span-to-depth ratio and with different arrangements of horizontal reinforcement, and Series-III specimens consists of six beams with different arrangements of vertical reinforcement i.e. the main variables are the shear span-to-depth ratio, of horizontal reinforcement and vertical reinforcement. Observations are made on failure modes and ultimate shear strength. Test results show that the beam specimens with a/d-ratio <= 1.8, the generation of shear capacity is significant. It is also shown that orthogonal web reinforcement comprising both vertical and horizontal reinforcement is the most efficient in enhancing the ultimate shear strength and the failure is in ductile mode The results from the experiments have been processed suitably to come out with empirical expressions for estimating the shear capacity of beams incorporating variables such as compressive strength of concrete, percentage of longitudinal and vertical steel/s, depth of beam in terms of shear span-to-depth ratio. Further, the comparisons of shear design provisions of four National codes viz.: (i) ACI 318-2002 (ii) CIRIA Guide-2, (iii) BS 8110-1997, (iv) IS 456-2000 for the prediction of shear strength of Transfer beam/s (shear span-to-depth ratio < 1.8), have been made with a view to seeing their goodness of fit against the experimental values.